Metabolomics Analysis Discovers Estrogen Altering Cell Proliferation via the Pentose Phosphate Pathway in Infertility Patient Endometria - Zheng, Yingxin; Zhu, Yuemeng; Zhuge, Ting; Li, Bin; Gu, Chao (Frontiers in Endocrinology, 2021)
Oestrogen therapy has been widely used as a supplementary treatment after hysteroscopy for infertility female patient due to its protective function that improves the endometrial regeneration and menstruation and inhibits recurrent adhesions and improve the conception rate. The endometrial protective function of such estrogen administration pre-operation is still controversial. We recruit twelve infertility patients who treated high dose estrogen before the hysteroscopy surgery. Using a cutting-edge metabolomic analysis, we observe the alterations of pentose phosphate pathway (PPP) intermediates in patient endometrial tissues. Using a endometrial cell, Ishikawa, we validate our clinical discovery and locate the Estrogen-ESR-G6PD-PPP axial function to promote the estrogen induced cell proliferation.